TRANSIENT TEST ANALYSIS OF THE FIRST HORIZONTAL WELL IN TELISA RESERVOIR TO MODEL THE RESERVOIR PERFORMANCE - Kunto Wibisono, R.
Abstract: Telisa formation in Minas Field is a calcareous, very-fined grained sandstone with up to 20% clay. This reservoir also contains carbonate which occurs both as grains and as cement. The clay mineralogy is illite. The clays occur as very thin laminae and as pore-throat linings. To optimize the oil recovery, a horizontal well was drilled in this reservoir. A pressure transient test was conducted in this well in order to identify the reservoir characteristic as well as its performance. The objective of this thesis is to analyze the horizontal well performance through its pressure transient behavior and to build a reservoir model and predict the reservoir as well as production performance based on parameters resulted from the pressure transient analysis. During the pressure transient analysis, a drawdown diagnostic plot was used to identify various flow regimes and a Horner plot was used to interpret the pressure build up data. The reservoir model was built using a homogeneous permeability and porosity based on the pressure transient analysis result. It is found that the pore volume needs to be greatly reduced to accommodate the laminating clay and carbonate. From the model, this well is predicted to be able to produce totally 109 MSTB during its 5 years production. During the transient test, the model is also found to be insensitive to the installation of blank liners as long as they are installed far enough from the electric submersible pump.